2003
DOI: 10.1126/science.1089543
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Fine Root Turnover on Forest NPP and Soil C Sequestration Potential

Abstract: Estimates of forest net primary production (NPP) demand accurate estimates of root production and turnover. We assessed root turnover with the use of an isotope tracer in two forest free-air carbon dioxide enrichment experiments. Growth at elevated carbon dioxide did not accelerate root turnover in either the pine or the hardwood forest. Turnover of fine root carbon varied from 1.2 to 9 years, depending on root diameter and dominant tree species. These long turnover times suggest that root production and turno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
399
4
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 450 publications
(430 citation statements)
references
References 20 publications
21
399
4
6
Order By: Relevance
“…C. arenaria did not seem to release appreciable amounts of this compound regardless of atmospheric CO 2 level (Figure 4). Although plant litter represents the dominant pathway by which plant C is transferred to soil, living roots also contribute significantly to this process through turnover of fine roots, sloughing of living cells and exudation (Matamala et al, 2003;Philips et al, 2006). Furthermore, root exudation probably exerts a disproportionate impact on rhizosphere communities, as it represents the most easily accessible C available to the soil microbes (Cardon, 1996).…”
Section: Antibiotic-production Genesmentioning
confidence: 99%
“…C. arenaria did not seem to release appreciable amounts of this compound regardless of atmospheric CO 2 level (Figure 4). Although plant litter represents the dominant pathway by which plant C is transferred to soil, living roots also contribute significantly to this process through turnover of fine roots, sloughing of living cells and exudation (Matamala et al, 2003;Philips et al, 2006). Furthermore, root exudation probably exerts a disproportionate impact on rhizosphere communities, as it represents the most easily accessible C available to the soil microbes (Cardon, 1996).…”
Section: Antibiotic-production Genesmentioning
confidence: 99%
“…In parallel, more in depth analysis of the eddy covariance observations are required to more fully exploit the information content of these datasets on hourly to decadal timescales. To improve the representation of carbon flow within ecosystems, comparison with other types of measurements is necessary, including analysis of existing datasets of leaf litter decomposition (Parton et al, 2007;Zhang et al, 2008), leaf lifespan (Reich et al, 2004), decomposition of coarse woody debris, and turnover of fine roots (e.g., Matamala et al, 2003), as well as soil carbon stocks and radiocarbon estimates of soil carbon turnover times. Regional estimates of aboveground live biomass, including the spatial inventory of North America developed by Blackard et al (2008), have the potential to constrain mortality and disturbance processes, when combined with measurements of NPP and allocation.…”
Section: Existing Gapsmentioning
confidence: 99%
“…Furthermore, our ability to observe directly and quantify roots in situ is limited (Majdi et al, 2005;Trumbore and Gaudinski, 2003) Estimates of C allocation to root growth and maintenance have been based on the assumption that fine roots turn over approximately annually (Jackson et al, 1997). However, measurements of isotopes in fine roots demonstrated that both the 14 C age (Gaudinski et al, 2001) and the incorporation rate of a continuous 13 C label (Matamala et al, 2003) in fine root C were inconsistent with an annual turnover. The various observations can be reconciled by assuming that fine roots are not a single homogeneous pool (Gaudinski et al, 2010;Guo et al, 2008;Strand et al, 2008;Tierney and Fahey, 2002;Trumbore, 2009).…”
Section: Introductionmentioning
confidence: 99%